Viscoelastic behavior of polycaprolactone/clay nanocomposites - Ludueña, Leandro Nicolás (2011)
The creep behavior of polycaprolactone and polycaprolactone/clay nanocomposites prepared by melt intercalation was studied. Sodium montmorillonite and organo-modified montmorillonite were used as reinforcement in order to analyze the effect of clay dispersion degree. Both a viscoelastic creep model named Burgers (four parameters) and an empirical method called Findley power law were applied to fit the experimental data (elastic, primary creep stage, and secondary creep stages). An additional effort was conducted to relate the parameter analysis of the Burgers model with the experimental behavior at each creep stage. The variation of the theoretical parameters illustrated the influence of the nanofillers on the experimental creep performance of the bulk matrix. Time?temperature superposition principle was used to predict the long-term behavior based on the short-term experimental data. The Findley power law model was also employed to reproduce the master curves. Both experimental curves and models demonstrated that the incorporation of the clay produces a significant improvement on the creep resistance at short times. This effect was higher for the best-dispersed nanocomposite. The latter result was strictly related to the great enhancement of the elastic behavior since in that case the time-dependent deformations were higher than those of the neat matrix.